A Global View of the U.S. Investment Position - Swiston, Andrew (IMF Working Papers; Working Paper ;, 2005)
This paper analyzes various indicators of the U.S. international investment position from a portfolio perspective. The 1990s saw a decline in home bias, which, coupled with rapid financial deepening, led to a large increase in gross international investment holdings. The home bias of non-U.S. investors declined more rapidly than that of U.S. investors, allowing the United States to finance a rising stock of net liabilities, even as foreign portfolios remained marketweight or underweight U.S. assets in each investment category. However, a comparison to other countries reveals that the U.S. net international investment position (NIIP) is large given the size of the economy and is deteriorating, especially through a growing negative net debt securities position.